Carbon Exchange, Storage and Sequestration - Högbom, Lars; Lehtonen, Aleksi; Nybakken, Line; Repo, Anna; Sarkkola, Sakari; Strömgren, Monika (Springer Nature Switzerland, 2025)
Boreal forests sequester and store large amounts of carbon both above and below ground. Forest management could influence carbon storage. Differences between upland soils and peatlands are important. In peatlands, large amounts of carbon are stored in the peat, making them more susceptible to differences in forest management. On peatlands, carbon balance is mostly determined by groundwater levels. Carbon storage on both upland and peat soils depends on harvest intensity since most carbon losses, apart from harvested forest products, come from decomposition of roots and logging residues. Scales in both space and time are both important considerations when estimating the effect on carbon balances.
Keywords: soil carbon; upland soil; peatlands; carbon storege; carbon sequestration